2021
DOI: 10.3233/bmr-200008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of equine riding on static and dynamic mechanical contraction of the thighs and trunk muscles in inactive women

Abstract: BACKGROUND AND OBJECTIVE: This study investigated whether equine riding affects static or dynamic mechanical contractions on the thighs and trunk muscles in inactive women. METHODS: Participants consisted of 30 women with a mean (SD) age of 21.06 (0.44) years. They were randomly allotted as follows: equine group (EQG, n= 15) and control group (CON, n= 15). Two types of muscle contraction properties in their thighs and trunk were measured through a tensiomyography (static muscle tester) and an isokinetic device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This mechanism becomes significant with changes in increased Tc and decreased Dm. Several researchers also suggested that a low Dm indicates a high muscle tone and excessive stiffness in the muscle structures, whereas an elevated Dm indicates a lack of muscle tone or the appearance of muscle fatigue [12,13,26]. Considering that Dm varies depending on the load of strength training, the recovery time between repetitions, and the type of muscle contraction, it can be estimated that the LESS IG analyzed in this study had a higher training volume than the MORE IG.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…This mechanism becomes significant with changes in increased Tc and decreased Dm. Several researchers also suggested that a low Dm indicates a high muscle tone and excessive stiffness in the muscle structures, whereas an elevated Dm indicates a lack of muscle tone or the appearance of muscle fatigue [12,13,26]. Considering that Dm varies depending on the load of strength training, the recovery time between repetitions, and the type of muscle contraction, it can be estimated that the LESS IG analyzed in this study had a higher training volume than the MORE IG.…”
Section: Discussionmentioning
confidence: 76%
“…Characteristically, the shape of the overall curve appears to collapse after the injury, which is due to the fact that muscle contraction does not proceed normally and rapidly [26,27]. The two parameters enable the muscular composition of the studied muscular groups to be increased [28], correlated with the increase in the contraction time, and the decrease in the muscular displacement amplitude [12,29]. These parameters have normal average values for Tc, namely, 32.83 ms, and for all muscular groups, the average Dm value is 8.17 mm [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were expected, because the gain in neuromuscular activation increased when the horse was in motion. The somatosensory, vestibular, and musculoskeletal systems stimulated by equine movement can influence postural tone distribution in the trunk (Park et al, 2021; Silva et al, 2021). In contrast, the lowest EMG values were recorded in the pre- and post-intervention moments when the horse was stationary.…”
Section: Discussionmentioning
confidence: 99%